Evaluación de diferentes niveles de zeolita en el control de patologías digestivas durante la etapa de producción en pollos broiler - Analuiza García, Marlon Javier (2025)
Zeolite is a natural mineral primarily composed of aluminosilicates, with a porous structure that allows it to adsorb toxins, heavy metals, and nitrogenous compounds such as ammonia. In poultry production, it has been evaluated as a dietary additive aimed at improving intestinal health and reducing the incidence of digestive disorders in Broiler chickens. These pathologies are a common concern in the poultry industry, causing significant economic losses due to increased mortality, poor weight gain, inefficient feed conversion, and overall decreased production performance. The objectives of this study were: 1) To evaluate the effect of different zeolite levels in reducing digestive pathologies, 2) To identify the optimal dosage for enhancing Broiler chicken performance, and 3) To determine the cost-benefit ratio of zeolite inclusion in poultry diets. The research was carried out in the poultry facilities of the Faculty of Agricultural Sciences at the State University of Bolívar, located in the parish of Gabriel Ignacio Veintimilla, Guaranda canton, using a Randomized Complete Block Design (RCBD) with four treatments and four replications. The results showed that the 2 cc/L zeolite treatment was the most effective, significantly improving weight gain, feed conversion, and reducing mortality caused by digestive disorders. In addition, intestinal pH remained stable, indicating a healthy digestive environment. From an economic perspective, this treatment also yielded the best cost-benefit ratio, proving to be viable and sustainable for commercial poultry production. It is concluded that zeolite, at appropriate levels represents an effective natural alternative to antibiotics, supporting a safer, more profitable, and sustainable poultry industry.